Penerapan Teknologi Progressive Web Apps pada Aplikasi Pembelajaran Al-Qur’an Metode Dirosa - Sitti Aisa; Nurul Aini; Imran Djafar; Asmah Akhriana (Computer Science and Information Technology, 2022)
Indonesia is a country with the largest Muslim population in the world. However, there are still many people who do not understand Islam itself, especially how to read the Qur'an correctly and correctly. In fact, the Qur'an itself discusses two major problems, the problem of this world and the problem of the hereafter. So it is very important for us as Muslims to learn it. DIROSA (Qur'an Education for Adults) is a systematic, layered and continuous model of Islamic counseling for beginner Muslims (men and women; adolescents, adults, grandparents; converts). With this method, adults who want to learn to read the Qur'an will easily and quickly understand it. The system design model is described in the form of UML (Unified Modeling Language) by making use case diagrams, class diagrams, and activity diagrams. So with the use of technology, create an application that can help adults learn to understand the reading of the Qur'an by inserting the DIROSA method using Progressive Web Apps technology to present easy-to-use applications and learning methods that also make it easier for adults to learn.